The Correlation Between Emotional Intelligence and Speaking Performance - Eliya Adelia; Andi Mangnguntungi Sudirman; Reski Yusrini Islamiah Yunus (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2022)
This research aims to find out the correlation between emotional intelligence and speaking performance. This research is quantitative research that uses the correlation as a method. The subject in this research is the second semester English education students at Cokroaminoto Palopo University. The instrument of this research is questionnaire and speaking test, the questionnaire used to know students’ emotional intelligence and speaking test used to know students’ speaking performance. The result of this research shows the significance value Sig. (2-tailed) is 0.312, because the significantly is higher than 0.05 (0.312 > 0.05), it can be concluded that there is no significant correlation between emotional intelligence and speaking performance (H0 is accepted and Ha is rejected) and also the researcher concluded that respondents have high emotional intelligence but very low correlation with speaking performance. It can be state that influential factor on speaking performance comes from linguistic problems.